The modern models of e-commerce organization: theoretical aspect (Economics and region, 2020)
The article explores the essence of the concept of "e-commerce". The basic models used in e-commerce are analyzed. Their development and dissemination are due to processes of globalization and rapid development of information technologies. This allows diversifying the business and increasing profitability at the current stage. The authors identify the disadvantages and benefits inherent to the major e-commerce participants.
Keywords: e-commerce; model; commerce; site; internet